The application of the 2D/3D electrical resistivity tomography (ERT) method in investigating the carbonate karst of the Zakrzówek Horst - Pasierb, Bernadetta (Geology, Geophysics and Environment, 2022)
A characteristic features of the geological structure of the Krakow area are tectonic horsts and grabens. The Zakrzówek Horst is one of the seven horst structures within the Krakow area, located in the south-western part of the area. It is built of Upper Jurassic limestones, where numerous karst caves have been developed. The caves of the Zakrzówek Horst probably form a system of interconnected caves. This hypothesis has been tested in the western region of the Zakrzówek Horst using the electrical resistivity tomography (ERT) method. The investigations were conducted in the parallel profile configuration as well as with the data processing procedure based on the 2D and 3D inversion. The results of these studies are an attempt to locate additional voids as well as fractured zones in the carbonate rock mass. The studies confirmed the hypothesis that the Jasna Cave is probably only a fragment of a vast cave system developed within the Zakrzówek Horst. As a result of the research carried out with the ERT method, the most prospective directions for future speleological research have been determined.